Croatian-German Conversation Dictionary from 1747 (Libellarium: journal for research in the field of information and related sciences, 2011)
The little Croatian-German dictionary titled Nemske skole navuk is printed on 32 pages of octavo format, without a cover page, and the data on the place and time of printing are contained in the colophon. It is kept at the Museum of Slavonia in Osijek. The data on entry into the inventory register is located at the inner side of the front cover page and reads: ‘Entered into the book property register p. 22, no. 278.’ The Dictionary was printed in Zagreb by Johann Baptista Weitz, and unlike the two large dictionaries that preceded it, Gazophylaciuma by Belostenac from 1740 and the Lexicon by Jambrešić from 1742, it was designed as a conversation dictionary with selected, i.e. more frequent words grouped by topics. The Dictionary has so far not been presented or analysed in a bibliographic, professional or scientific manner; therefore, it is completely unknown to Croatian science, which was the reason for publishing its re-print in this issue of ‘Libellarium’. (Zoran Velagić)